A Needs Analysis-Based ESP Model for Islamic Education Management: Integrating Linguistic Expertise and Professional Practice - Fikri Asih Wigati; Nia Pujiawati (Journal of Educational Sciences, 2026)
This study examines the gap between theoretical English language learning and practical application in Islamic education.English language teachers lack specialized expertise in the subject matter being taught, while Islamic education practitioners have real-world experience but limited teaching skills. This study used a mixed approach to examine the needs of ESP instructional design in an Islamic Education Management program. A survey was conducted with 60 students to assess their specific English language needs, while in-depth interviews with 10 practitioners working in Islamic educational institutions revealed the professional communication demands they face. The needs analysis revealed a significant gap between students' current linguistic abilities and the professional communication needs in an Islamic education environment. Students demonstrated high motivation for practical skills but lacked exposure to authentic workplace communication scenarios. Based on these findings, the study developed an innovative collaborative ESP model that integrates English language learning with practical application through systematic collaboration between English language teachers and practitioners. This model addresses fundamental incongruities in traditional ESP approaches by combining linguistic expertise and authentic professional experience, producing work-ready graduates with language competency and professional communication skills.